Ultrasound surveillance for hepatocellular carcinoma: real-life performance in a hepatology outpatient clinic (Swiss Medical Weekly, 2015)
QUESTIONS: Regular surveillance of patients at risk for hepatocellular carcinoma (HCC) has been recommended by international guidelines and is practiced in many hepatology clinics. However, little is known about the effectiveness and the costs of 6 monthly ultrasound surveillance. METHODS: Clinical charts, ultrasound reports and reports of additional examinations (computed tomography, magnetic resonance imaging, liver biopsy) were systematically reviewed. The tumour stage of HCC detected in the surveillance programme was compared with stages of patients not surveyed. The number needed to survey to detect a HCC and the costs per detected HCC were calculated. RESULTS: In the 2-year period 2011–2012, 696 ultrasound examinations in 285 patients were performed in the hepatology outpatient clinic of the University Hospital Basel, Switzerland. Focal lesions were detected by ultrasound in 88 of the 285 patients. Nine of them had a newly diagnosed HCC. All of them were at early stage (Barcelona Clinic Liver Cancer staging 0 or A) and 8 of 9 fulfilled Milan Criteria. In this 2-year surveillance period, the number needed to screen was 32 patients. The calculated costs per detected HCC were 29 701 Swiss francs. CONCLUSIONS: In this retrospective analysis, HCC surveillance resulted in the detection of HCCs in an early stage. The number needed to screen and the costs of the surveillance are reasonably low.